Brief Report: A Preliminary Investigation of a Mindful Breathing Intervention to Increase Academic Engagement in an Alternative Educational Setting. (August 2018) - Minkos, Marlena L.; Chafouleas, Sandra M.; Bray, Melissa A.; LaSalle, Tamika P.
The current study used a multiple-baseline across subjects design to examine the effect of a daily, audio-delivered, mindful breathing intervention on adolescents with emotional and behavioral difficulties attending an alternative educational setting. Academic engagement served as the primary dependent variable, with disruptive behavior, feasibility, and acceptability serving as secondary dependent variables. Four students entered the baseline phase; however, only two students entered the intervention phase. Results indicated that participants displayed increases in academic engagement as measured by both direct behavior rating and systematic direct observation that were maintained at 6-week follow-up. Decreases in disruptive behavior were also observed. Because the effects were not replicated three times, changes cannot be directly attributed to the intervention. In addition, teachers and students perceived the intervention to be both feasible and acceptable. Implications of the findings are discussed.